Protective Effect of Diospyros kaki against Glucose-Oxygen-Serum Deprivation-Induced PC12 Cells Injury. (28th January 2016) - Forouzanfar, Fatemeh; Torabi, Shaghayegh; Askari, Vahid R.; Asadpour, Elham; Sadeghnia, Hamid R.
Abstract : Ischemic cerebrovascular disease is one of the most common causes of death in the world. Recent interests have been focused on natural antioxidants and anti-inflammatory agents as potentially useful neuroprotective agents. Diospyros kaki (persimmon) has been shown to exert anti-inflammatory, antioxidant, and antineoplastic effects. However, its effects on ischemic damage have not been evaluated. Here, we used an in vitro model of cerebral ischemia and studied the effects of hydroalcoholic extract of peel (PeHE) and fruit pulp (PuHE) of persimmon on cell viability and markers of oxidative damage mainly intracellular reactive oxygen species (ROS) induced by glucose-oxygen-serum deprivation (GOSD) in PC12 cells. GOSD for 6 h produced significant cell death which was accompanied by increased levels of ROS. Pretreatment with different concentrations of PeHE and PuHE (0–500 μ g/mL) for 2 and 24 h markedly restored these changes only at high concentrations. However, no significant differences were seen in the protection against ischemic insult between different extracts and the time of exposure. The experimental results suggest that persimmon protects the PC12 cells from GOSD-induced injury via antioxidant mechanisms. Our findings might raise the possibility of potential therapeutic application of persimmon for managing cerebral ischemic and other neurodegenerative disorders.